Revitalisasi Kuliner Bingen Palembang Sebagai Sarana Pelestarian Kuliner Tradisional Palembang Dan Peningkatan Kualitas Ekonomi Masyarakat Seberang Ulu II Kota Palembang - Putri Anindhita Faradila; fitriya Fitriya; abdul Basyith (Jurnal Nasional Pengabdian Masyarakat, 2022)
The city of Palembang is the capital of the Province of South Sumatra. The city of Palembang is a city where there is a kingdom that controls the Archipelago and the Malay Peninsula in the 9th Century, namely the Sriwijaya Kingdom. The history of the city of Palembang is inseparable from a variety of multi-ethnic Javanese, Malay, Chinese, Arabic and other ethnic groups which gave birth to multi-cultural arts and traditional foods typical of the city of Palembang. Traditional in Palembang language is called the word "BINGEN". Everything that contains traditional elements will be called bingen. At present both art and traditional food typical of the city of Palembang have begun to erode the flow of modernization. For example, young people today prefer western-style art and food or more so-called "westernization". There are various types of traditional specialties of Palembang City that are rich in artistic value, cultural values, nutritional value and economic value. However, the traditional foods (bingen food) of Palembang City have no selling value to both local and international communities. Although there are some typical Palembang foods that are known as pempek, model and tekwan, but foods like traditional cakes are not so popular today among the younger generation, especially generation Y, Z and millennial because these generations no longer know the variety of cakes - traditional Palembang cake.Palembang traditional cakes are a cultural heritage that needs to be preserved as an asset to the Palembang region because the cakes have a very high cultural history. Aside from being Palembang's regional assets, these cakes can be a characteristic of Palembang and a means of improving the economic quality of the Palembang community where the number of both local and foreign tourists increased in 2016 by 10.1%, of which 99% were local tourists and 1% were foreign tourists. The number of local tourists alone increased by 10% in 2016 while foreign tourists increased by 33.1% in 2016. So this shows that the city of Palembang is considered a city destination for tourism destinations, especially culinary tourism because Palembang has little natural tourism.Palembang City consists of 16 Subdistricts, and Seberang Ulu II Subdistrict ranks 7th which has the most population with an invisible unemployment rate of 87%, all of which are women with a poverty rate of 7.8% and are in the order of 7 sub-districts that have the most pre-prosperous families from 16 sub-districts in Palembang City. With the erosion of various Palembang bingen cakes which have high historical value and various social economic problems such as high unemployment and poverty levels, it is necessary to revitalize Palembang bingen cakes so that they are not extinct by providing training and counseling on various cakes. Palembang Bingen cake to the community in Seberang Ulu II Subdistrict, especially mothers, which in turn the mothers who are cadres can become trainers in other sub-districts in Palembang and open new entrepreneurs in the Palembang bingen cakes so that they can preserve cakes -kue Palembang bingen, they can help improve the family economy and ultimately reduce unemployment and poverty levels in the city of Palembang. The objectives of the Palembang bingen cake revitalization activities are (1) the emergence of new entrepreneurs in the community of Palembang bingen cake makers; (2) Establishment of the Palembang bingen cake business group; (3) The creation of cooperation between the Palembang bingen cake business groups and the UMKM service, industry service, tourism and local government offices in Palembang City as well as hotels in Palembang City to support the sustainability of this program.